Trend in physical activity patterns of pregnant women living in Brazilian capitals - Rinaldi, Ana Elisa Madalena; de Paula, Janaína Aparecida; Almeida, Maiara Aparecida Miálich [UNESP]; Corrente, José Eduardo [UNESP]; Carvalhaes, Maria Antonieta Barros Leite [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
OBJECTIVES: To describe the trend of physical activity (PhA) in four domains performed by pregnant women living in Brazilian capitals and the Federal District (FD) and to verify the association between sociodemographic factors and the practice of leisure-time physical activity between 2007 and 2017. METHODS: Time trend study carried out with data from the Surveillance System of Risk Factors for chronic diseases by telephone survey (Vigitel). A total of 3,730 pregnant women were interviewed in the period, considering sociodemographic variables (age, macro-region, work, marital status, schooling, skin color) and physical activity in the four domains (leisure-time, work, commuting, domestic – yes/no). For pregnant women who performed leisure-time physical activity, its duration was inquired, expressed in the variable PhA ≥ 150 minutes/week (yes/no). The time trend was evaluated by variance-weighted linear regression (average annual variation was expressed in percentage points – pp) and the association of sociodemographic factors with leisure-time physical activity by Poisson regression, with prevalence ratio (PR) estimation. RESULTS: The prevalence of pregnant women with 12 years of schooling or more increased in the analyzed period (+1.37 pp/year), as well as the prevalence of pregnant women with more than 35 years of age (+1.11 pp/year) and those who work (+0.75 pp/year). The prevalence of leisure-time physical activity by pregnant women increased from 29.3% in 2007 to 37.6% in 2017 (+1.37 pp/year), and of PhA ≥ 150min/week from 2.3% to 20.6% (+2.33 pp/year), respectively, and there was a reduction in domestic physical activities from 63.9% to 38.9% (-1.65 pp/year). The prevalence of leisure-time physical activity was higher among pregnant women with more than 12 years of schooling (PR = 2.22; 95%CI: 1.73–2.84) as compared to those with less than 8 years of age, and lower among black/brown/indigenous pregnant women, compared to white/yellow ones (PR = 0.87; 95%CI: 0.78–0.97). The prevalence of PhA ≥ 150min/week increased according to years of schooling and age. CONCLUSIONS: The prevalence of leisure-time physical activity and its performance for ≥ 150 minutes/week increased in the analyzed period, and both were directly associated with greater schooling.
Keywords: Exercise; Health surveys; Leisure activities; Pregnant women; Socioeconomic factors